Onchocerca volvulus and epilepsy: A comprehensive review using the Bradford Hill criteria for causation. - Robert Colebunders; Alfred K Njamnshi; Sonia Menon; Charles R Newton; An Hotterbeekx; Pierre-Marie Preux; Adrian Hopkins; Michel Vaillant; Joseph Nelson Siewe Fodjo (Public Library of Science (PLoS), 2021)
Background The possibility that onchocerciasis may cause epilepsy has been suggested for a long time, but thus far, an etiological link has not been universally accepted. The objective of this review is to critically appraise the relationship between Onchocerca volvulus and epilepsy and subsequently apply the Bradford Hill criteria to further evaluate the likelihood of a causal association. Methods PubMed and gray literature published until September 15, 2020, were searched and findings from original research were synthesized. Adherence to the 9 Bradford Hill criteria in the context of onchocerciasis and epilepsy was determined to assess whether the criteria are met to strengthen the evidence base for a causal link between infection with O. volvulus and epilepsy, including the nodding syndrome. Results Onchocerciasis as a risk factor for epilepsy meets the following Bradford Hill criteria for causality: strength of the association, consistency, temporality, and biological gradient. There is weaker evidence supporting causality based on the specificity, plausibility, coherence, and analogy criteria. There is little experimental evidence. Considering the Bradford Hill criteria, available data suggest that under certain conditions (high microfilarial load, timing of infection, and perhaps genetic predisposition), onchocerciasis is likely to cause epilepsy including nodding and Nakalanga syndromes. Conclusion Applying the Bradford Hill criteria suggests consistent epidemiological evidence that O. volvulus infection is a trigger of epilepsy. However, the pathophysiological mechanisms responsible for seizure induction still need to be elucidated.